PHYSICAL AND BIOLOGICAL PROPERTIES OF INFLUENZA VIRUS COMPONENTS OBTAINED AFTER ETHER TREATMENT - Davenport, Fred M. (The Rockefeller University Press, 1960)
The Rostock strain of fowl plague, the swine, A, A', and Asian strains of influenza A as well as their hemagglutinin and internal s antigen subunits obtained after ether splitting, were found to be morphologically indistinguishable when examined simultaneously. Hemagglutinin fractions reacted in a highly strain specific manner when tested by hemagglutination inhibition or by complement fixation using sera obtained after infection. With the same sera internal s antigen fractions were shown to be serologically distinguishable by complement fixation. This observation may stimulate interest in the feasibility of employing immunologic techniques for the study of nucleoproteins. The significance of the findings reported is discussed.